2020
DOI: 10.1038/s41598-020-78361-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of femtosecond laser-assisted anterior capsulotomy in the presence of ophthalmic viscoelastic devices (OVDs)

Abstract: The introduction of femtosecond laser-assisted cataract surgery is an alternative approach to conventional cataract surgery. Our study aimed to determine the effectiveness of femtosecond laser-assisted capsulotomy in the presence of different ophthalmic viscoelastic devices (OVDs) in the anterior chamber. Fresh porcine eyes (n = 96) underwent LDV Z8-assisted anterior capsulotomy, either in the presence of an OVD (Viscoat, Provisc, Healon, Healon GV or HPMC) or without, using 90% and 150% energies respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The absorption coefficient is an intrinsic physical property of a material, aside from its refractive index or viscosity, and as 13.5% laser power attenuation is considerably large, absorption through OVDs must be considered. Although the probability of achieving a complete capsulotomy increases when 150% of energy is used, as indicated by results of the previous study, 21 an increase in laser energy can adversely affect capsulorhexis, such as capsular adhesion and an increased risk of anterior-capsular tags. 22 Therefore, it is important to increase laser energy appropriately through accurate calculations.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The absorption coefficient is an intrinsic physical property of a material, aside from its refractive index or viscosity, and as 13.5% laser power attenuation is considerably large, absorption through OVDs must be considered. Although the probability of achieving a complete capsulotomy increases when 150% of energy is used, as indicated by results of the previous study, 21 an increase in laser energy can adversely affect capsulorhexis, such as capsular adhesion and an increased risk of anterior-capsular tags. 22 Therefore, it is important to increase laser energy appropriately through accurate calculations.…”
Section: Discussionmentioning
confidence: 84%
“… 19 In a recent study, an incomplete capsulotomy was observed more frequently when using a high-viscosity OVD than when using a low-viscosity OVD, suggesting that high-viscosity OVDs could reduce the efficacy of the femtosecond laser by prolonging the lifetime of the bubble and reducing the impact velocity. 20 , 21 Therefore, in addition to our results, the effect of cavitation bubbles should be considered; the relationship between the viscosity of OVD and bubble generation will be investigated through future studies using a streak camera with different laser powers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the current study, we showed that FSL capsulotomy using a low-energy FSL system did not result in the increased generation of intracameral free radicals, and an increase in the capsulotomy energy level did not lead to further increases in free radicals. An increase in the capsulotomy energy level is useful in the case of capsulotomy formation in the presence of an OVD in the anterior chamber [ 25 , 26 ]. Increases in the FSL capsulotomy energy levels did lead to increased concentrations of pro-inflammatory IL-8 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 study compared the capsulotomy quality in low-energy versus high-energy FLACS, and found that in 200 eyes ( n = 100 for each group), a lower energy FLACS system provided significantly better results for completeness of the capsulotomy, intraoperative miosis, and subconjunctival hemorrhage [43 ▪ ]. However, another study comparing femtosecond laser energies in porcine eyes with different ophthalmic viscoelastic devices ( n = 96) found that higher energy settings improve capsulotomy results (circularity and tag-parameters) across all OVDs [44]. An analysis of 3834 FLACS capsulotomies found that anterior capsule tear rates are low, and can be reduced by an increase in vertical spacing; tear rates were 0.79, 0.35, and 0.09% respectively for the 10, 15, and 20 μm vertical spacing groups [45].…”
Section: Femtosecond Laser Capsulotomymentioning
confidence: 99%